BALESARI CULTURE AND LANGUAGE (BCL) SEBAGAI KATALISATOR DESA WANA WISATA BALESARI - Faradisa, Farikah; Katrini, Yulia Esti; Baihaqi, Imam (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2017)
Wana Wisata of Balesari village has huge potential to be developed into a national and even international tourist village. Balesari village is also categorized as a virgin, and it still has many local wisdoms that can be a special attraction for domestic visitors and also foreign tourists if the community of Balesari can manage it properly and maximally.. The focus of the contribution of Tidar University to the community is to serve the community to support the development of rural areas, one of them is Wana Wisata of Balesari Village. The development of villages is focused on Balesari Culture and Language activities that is cultural and linguistic conservation that manifests in awareness of activities, training, and cultural and linguistic assistance to become a tourist icon in Balesari village. In addition gradually over a period of 3 years, Balesari Culture and Language programs will also conserve the culture and language based on local wisdom in the village of Balesari gradually as a catalyst that will participate in improving the development of Balesari Wana Tourism Village.Â Desa Wana Wisata Balesari memiliki potensi yang sangat besar untuk dapat dikembangkan menjadi sebuah desa wisata bertaraf nasional bahkan internasional. Desa Balesari juga dikategorikan masih perawan, masih terdapat banyak kearifan lokal yang dapat menjadi daya tarik tersendiri bagi para pengunjung domestik apalagi wisatawan asing apabila masyarakat dapat mengelolanya dengan baik, maksimal, dan profesional. Fokus kontribusi Universitas Tidar kepada masyarakat adalah melakukan pengabdian kepada masyarakat untuk mendukung pembangunan wilayah perdesaan salah satunya adalah Desa Wana Wisata Balesari. Pembangunan desa tersebut difokuskan dalam kegiatan Balesari Culture and Language yaitu konservasi budaya dan bahasa yang mewujud dalam kegiatan penyadaran, pelatihan, dan pendampingan budaya dan bahasa agar menjadi ikon wisata di desa Balesari. Selain itu secara bertahap dalam jangka waktu 3 tahun, program Balesari Culture and Language juga akan melakukan konservasi budaya dan bahasa berbasis kearifan lokal yang terdapat di desa Balesari secara bertahap sebagai katalisator yang akan ikut mempercapat laju perkembangan Desa Wana Wisata Balesari.